A Digital Transformation, R&D Expenditure, and Business Model Innovation: Drivers of Firm Value in the Digital Economy Era - A. Achmad Danial Latief Buleng; Yohanes Zefnath Warkula; Busman (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the effect of Digital Transformation, R&D Expenditure, and Business Model Innovation on Firm Value among technology companies listed on the Indonesia Stock Exchange for the 2023–2025 period. A quantitative approach with multiple linear regression was employed. Using purposive sampling, 34 companies were selected, yielding 102 observations. Firm value was measured using Tobin's Q. Results indicate that Digital Transformation and Business Model Innovation positively and significantly affect firm value, while R&D Expenditure exerts a significant negative effect. Simultaneously, all variables significantly influence firm value with a model predictive capacity of 77.4%. These findings confirm the Resource-Based View that digital capabilities and business model innovation constitute primary strategic resources driving value creation in technology firms